2003
DOI: 10.1128/jcm.41.11.4955-4960.2003
|View full text |Cite
|
Sign up to set email alerts
|

C 6 Test as an Indicator of Therapy Outcome for Patients with Localized or Disseminated Lyme Borreliosis

Abstract: Management of Lyme disease would benefit from a test to assess therapy outcome. Such a test could be employed to ascertain if treatment of early Lyme disease was successful and would be helpful to clinicians assessing patients with lingering posttreatment symptoms. We reported recently that levels of the antibody to C 6 , a Borrelia burgdorferi-derived peptide that is used as an antigen in the C 6 -Lyme diagnostic test, declined after successful antibiotic treatment of Lyme borreliosis patients. We assessed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
21
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 19 publications
6
21
0
Order By: Relevance
“…Philipp et al reported that 80% of a subset of patients treated for early localized or disseminated LB had a Ն4-fold decrease in their reciprocal geometric mean titers to C6 at 6 months or thereafter (255). Other studies have not confirmed these findings.…”
Section: Immunologic Diagnosis Of B Burgdorferi Sensu Lato Infectionmentioning
confidence: 61%
See 1 more Smart Citation
“…Philipp et al reported that 80% of a subset of patients treated for early localized or disseminated LB had a Ն4-fold decrease in their reciprocal geometric mean titers to C6 at 6 months or thereafter (255). Other studies have not confirmed these findings.…”
Section: Immunologic Diagnosis Of B Burgdorferi Sensu Lato Infectionmentioning
confidence: 61%
“…Those authors also reported that in another group of patients, 50% of those with early LB and 83% of those with late LB still had detectable C6 reactivity 8 to 15 years after treatment. Likely explanations for the discrepancies in the findings of Philipp and Peltomaa include differences in serum dilutions used to calculate the decline in antibodies, whether patients had sufficient titers at baseline to permit detection of a fourfold decline at least 6 months later, and/or the patient populations studied (250,255).…”
Section: Immunologic Diagnosis Of B Burgdorferi Sensu Lato Infectionmentioning
confidence: 99%
“…Two of the most commonly used tests for diagnosis in North America are (i) the twotier test, which includes an enzyme-linked immunosorbent assay (ELISA) and Western blotting using antigen derived from wholecell lysates, and (ii) the C6 test, which detects antibodies to a specific peptide within a conserved region of the B. burgdorferi antigen VlsE (5,30,32). The C6 test has also been used experimentally for evaluation of treatment efficacy (36,37).…”
mentioning
confidence: 99%
“…Since the handling time is minimal, the CLIA is more cost-effective as compared to conventional ELISAs and thus is an alternative for large scale laboratories. In the light of that convalescence samples sometimes are required to prove LD [6], the CLIA is an affordable option. In conclusion, the Liaison Borrelia CLIA is a reliable screening test for automatization and is comparable with the VlsE/C6 ELISA.…”
mentioning
confidence: 99%
“…Borrelia Outer surface protein C (OspC) [3] and Vmplike sequence expressed (VlsE) [4] are two plasmid encoded membrane proteins that both are immunodominant antigens. Furthermore, VlsE consists of one invariable region (IR6), which is extraordinary immunodominant [5,6]. Other antigens that have been useful in serology are p39 and p83 [7].…”
mentioning
confidence: 99%